The Role of Sleep and Sleep Disorders in the Development, Diagnosis, and Management of Neurocognitive Disorders - Miller, Michelle A. (Frontiers in Neurology, 2015)
It is becoming increasingly apparent that sleep plays an important role in the maintenance, disease prevention, repair and restoration of both mind and body. The sleep and wake cycles are controlled by the pacemaker activity of the superchiasmic nucleus in the hypothalamus but can be disrupted by diseases of the nervous system causing disordered sleep. A lack of sleep has been associated with an increase in all–cause mortality. Likewise, sleep disturbances and sleep disorders may disrupt neuronal pathways and have an impact on neurological diseases. Sleep deprivation studies in normal subjects demonstrate that a lack of sleep can cause attention and working memory impairment. Moreover, if untreated sleep disturbances and sleep disorders such as Obstructive Sleep Apnoe (OSA) can also lead to cognitive impairment. Poor sleep and sleep disorders may present a significant risk factor for the development of dementia. In this review, the underlying mechanisms and the role of sleep and sleep disorders in the development of neurocognitive disorders (dementia and Mild Cognitive Impairment (MCI)) and, how the presence of sleep disorders could direct the process of diagnosis and management of neurocognitive disorders will be discussed.